2020
DOI: 10.1001/jama.2019.22190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress Ulcer Prophylaxis With Proton Pump Inhibitors vs Histamine-2 Receptor Blockers on In-Hospital Mortality Among ICU Patients Receiving Invasive Mechanical Ventilation

Abstract: IMPORTANCE Proton pump inhibitors (PPIs) or histamine-2 receptor blockers (H 2 RBs) are often prescribed for patients as stress ulcer prophylaxis drugs in the intensive care unit (ICU). The comparative effect of these drugs on mortality is unknown. OBJECTIVE To compare in-hospital mortality rates using PPIs vs H 2 RBs for stress ulcer prophylaxis.DESIGN, SETTING, AND PARTICIPANTS Cluster crossover randomized clinical trial conducted at 50 ICUs in 5 countries between August 2016 and January 2019. Patients requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 19 publications
4
76
0
5
Order By: Relevance
“…23 Our results showed no significant differences for in-hospital mortality or the proportions of patients requiring endoscopic haemostasis, similar to results in previous randomised controlled trials. [24][25][26] Some previous studies have shown conflicting results regarding the efficacy of PPIs and H 2 RAs for stress ulcer prophylaxis. 7 27 In the present study, we found no significant difference in C. difficile infection rates between patients receiving PPIs versus H 2 RAs for stress ulcer prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our results showed no significant differences for in-hospital mortality or the proportions of patients requiring endoscopic haemostasis, similar to results in previous randomised controlled trials. [24][25][26] Some previous studies have shown conflicting results regarding the efficacy of PPIs and H 2 RAs for stress ulcer prophylaxis. 7 27 In the present study, we found no significant difference in C. difficile infection rates between patients receiving PPIs versus H 2 RAs for stress ulcer prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In other scenarios, different combinations may be acceptable. Some hypothetical scenarios are shown in Table 2 ( 14 , 25 , 27 29 ). Consider previous trials and or other valid external evidence.…”
Section: Proposed Guidance For Conducting and Reporting A Bayesian Rementioning
confidence: 99%
“…Based on the available evidence, we surmise that, although considerable uncertainty remains, the inferences from SUP-ICU and PEPTIC are consistent with the hypothesis that PPIs increase the risk of death in patients with higher illness severity. While, the overall evidence that PPIs reduce upper GI bleeding in the critically ill is unequivocal [5,15], it appears that most upper GI bleeds are not fatal, and the attributable mortality from such bleeds appears to be low [16]. Therefore, we suspect that most patients would exchange the small increased risk of upper GI bleeding to avoid a therapy that might increase their risk of death, despite the uncertainty.…”
mentioning
confidence: 97%
“…The results of the analysis by Granholm and colleagues [13] are particularly compelling when viewed together with the recently published Proton Pump Inhibitors versus Histamine-2 Receptor Blockers for Ulcer Prophylaxis Therapy in the Intensive Care Unit (PEPTIC) study [15]. The PEPTIC trial was a randomized, open-label, cluster-crossover trial that compared PPIs and histamine 2 receptor blockers (H 2 RBs) for stress ulcer prophylaxis in 26,982 mechanically ventilated adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation